O19.4 Awareness and interpretation of the ending hiv campaign and changing attitudes about treatment as prevention in an online cohort of msm. (13th September 2015) - Asselin, J; Wilkinson, A; Vella, A; Batrouney, C; Hellard, M; Pedrana, A; Stoové, M
Abstract : Introduction: Treatment as prevention (TAP) has become a key part of HIV control strategies in Australia. Ending HIV was launched in September 2013 as a combination prevention campaign with three messages: HIV testing, HIV treatment, and condom-reinforcement. The Burnet Institute has maintained a HIV prevention evaluation online cohort of men who have sex with men. We compare pre- and post-campaign evaluation surveys to assess Ending HIV campaign awareness and changes in campaign-related attitudes and beliefs. Methods: Participants were surveyed in August 2013 (S1, pre- Ending HIV implementation) and July 2014 (S2, post- Ending HIV implementation). Campaign recall and message recognition were assessed at S2, alongside S1 to S2 changes in attitudes and beliefs regarding a range of prevention topics, including TaP. Results: There were 353 respondents at S1 and 328 at S2; 193 completed both surveys. 158 respondents (48%) were aware of Ending HIV at S2, of who 87 (55%) correctly recalled at least one campaign message. Most commonly recalled messages referenced HIV testing (58%), followed by HIV treatment (37%) and condom-reinforcement (29%). Significant increases were seen in the proportion of HIV-negative men reporting positive changes in attitudes/beliefs in 7 out of 9 statements about TaP (p < 0.05). Proportional increases ranged from 5.0–17.0%, and highest for agreeing that PrEP is effective for HIV prevention (17%) and disagreeing that people should delay treatment until absolutely necessary (12%). Changes in attitudes and beliefs did not differ significantly by campaign awareness at S2. Conclusion: While awareness of Ending HIV is encouraging, comprehension of different combination prevention messages was inconsistent and modest for some messages. Predominant shifts in beliefs about TAP are likely to be driven by influences beyond campaign exposure. Future implementation of Ending HIV and associated prevention campaigns should ensure sufficient emphasis on primary prevention and early treatment messages as a part of combination prevention. Disclosure of interest statement: All authors have no conflicts to declare. The Victorian Department of Health funds the implementation of the Ending HIV campaign by the Victorian AIDS Council, and the evaluation of HIV prevention campaigns by the Burnet Institute. The authors would like to acknowledge the NHMRC who provide funding to Margaret Hellard as a Senior Research Fellow, Anna Wilkinson as a public health scholarship recipient, Alisa Pedrana through the Sidney Sax Post-Doctoral Fellowship and Mark Stoové through a Career Development Fellowship. The authors gratefully acknowledge the contribution to this work of Victorian Operational Infrastructure Support Program received by the Burnet Institute.